Downstream migration of Salmo salar and S. trutta smolts in two regulated northern Swedish rivers - Rivinoja, Peter; Leonardsson, K; Lundquist, Hans; Kiviloog, Jaan; Bergdahl, Lars; Brydsten, L (2004)
The downstream migration of Atlantic salmon and anadromous brown trout smolts was studied in two flow controlled northern Swedish rivers. The annual mean flow in Umeälven and Piteälven is c. 430 m3/s and c. 150 m3/s, respectively. Water power constructions located in the lower parts of these rivers may hinder or kill downstream migrating fish. Naturally produced salmon smolts in these rivers have two alternatives for passage of the water power constructions when they undertake their seasonally timed seaward migration in may-june: a) passing the turbines, or b) pass through the spill-way over the dam. Existing power-stations in Stornorrfors (Umeälven) use Francis turbines while Sikfors (Piteälven) use Kaplan turbines. In spring 2002 and 2003 a total of 90 Atlantic salmon and 56 brown trout two-year old hatchery-reared smolts were radio tagged with internal esophageal, individually coded radio transmitters (ATS). Trout were significantly larger (average length: 23.8 cm) than salmon (19.7 cm) (t-test, p<0.01). One to two days post-tagging the fish were released upstream the dammed areas, c. 5.0 km above Stornorrfors dam and c. 2.5 km above Sikfors dam, respectively. Their downstream migration routes were tracked both manually and with automatic listening stations in the horizontal plane (2-dimensional). Simultaneously, velocity profiles were measured in selected cross-sections using an Acoustic Doppler Profiler (ADP) applied to depth measurements giving a digitalised GIS-map over the dammed areas. Our main findings from the telemetry trackings, depth- and flow-measurements, and flow simulation show that the downstream migrating smolts move in the main flow in the river where the highest water velocities were registered. This subsequently resulted that fish entered the power-station, and did not pass downstream over spillways via dams or the fish ladders. The discharge ratio between power-station and spillway, with excess of water passing the power-station, guided fish to pass the turbines giving an extra ...